Mapping out overlapping connectivity patterns - Myrthe Faber; Koen V Haak (eLife)
Untangling the functional organisation of a brain region crucial for memory and learning helps reveal how individual differences are linked to variations in recall ability, aging and dopamine receptor distribution.